Different expression of three WRKY genes under simultaneous biotic and abiotic stresses in the root of wheat - Mirakhorli, Neda; Ahmadi, Mahin; Arkan, Mozhgan; Shabani, Leila; Ansari, Omid; Dababat, Abdelfattah A. (Pleiades Publishing, Inc., 2025)
Wheat (Triticum aestivum L.) is the most widely grown crop in the world. It grows under different climatic and agronomic conditions and faces various biotic and abiotic stresses. To cope and survive under these conditions, wheat uses a variety of defense and tolerance mechanisms. These mechanisms involve many genes and regulatory factors related to a network that causes different expression patterns of genes under different conditions. This study investigated the expression pattern of three transcription factor genes, WRKY29, WRKY53, and WRKY71, under both biotic and abiotic stress conditions. These genes were identified as stress-responsive genes by meta-analysis studies. Stresses include Heterodera filipjevi, Fusarium culmorum, and drought which were applied individually, double, and triple simultaneously. The expression of these genes under the introduced stress conditions was compared with the levels of antioxidant enzymes and traits of yield components in the two-wheat accession, 2–49 (resistant to Fusarium), “Silverstar” (resistant to Heterodera). It was found that drought as abiotic stress is the main factor in increasing the expression level of the three WRKY genes. One week after double simultaneous stress drought plus Heterodera in “Silverstar” (resistant to Heterodera) accession, the highest gene expression was obtained. But the level of expression decreased in triple simultaneous stress (drought + Heterodera + Fusarium) which caused damage and reduced the yield components traits. The level of gene expression was reduced under triple stress because of the antagonistic effect of fungus on nematodes and different pathways of fungal resistance and drought tolerance in wheat. This accession was susceptible to fungal stress and had the lowest gene expression under this stress. Accession 2–49 (resistant to Fusarium), the highest gene expression was in fungal stress. Since 2–49 was known as a drought-resistant accession, the WRKY gene expression was also high in drought stress. However, different stress combinations cause unpredictable plant responses, by studying the pattern expression of genes involved in resistance pathways, the potential of the plant can be understood generally.